PENGARUH MINUMAN JAHE MERAH TERHADAP PERUBAHAN NYERI DISMINORHEA - Rostina Pohan (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2022)
Menstruation is a natural occurrence that occurs every month for a woman. Almost all women must have experienced menstrual pain with different levels. To overcome dysmenorrhea, analgesic or anti-inflammatory drugs can be given or herbal therapy with traditional medicines that are believed to have efficacy derived from plant materials. One of the therapies to overcome dysmenorrhea is to use traditional medicine, only ginger (ginger). Ginger is as effective as mefenamic acid and ibuprofen for reducing dysmenorrhea. This study aims to determine the effect of giving red ginger to changes in dysmenorrhea pain in students at SMP. Negeri 13 Tanjungbala as many as 32 students. The method used in this study used an experimental research design with a quasi-experimental study design Pretest-posttest Non Equivalent Control Group Design. analysis of this study using the Wilcoxon test. Results: From the analysis of changes in dysmenorrhea pain before and after being given red ginger, the results were p = 0.000 (p <0.05). Conclusion: Giving red ginger has an effect on reducing dysmenorrhea pain in female students at SMP Negeri 13 Tanjungbalai City